2021
DOI: 10.3389/fmed.2021.752956
|View full text |Cite
|
Sign up to set email alerts
|

Research Trends and Hotspots of Extracorporeal Membrane Oxygenation: A 10-Year Bibliometric Study and Visualization Analysis

Abstract: Objective: To determine the research hotspots and trends in the field of extracorporeal membrane oxygenation (ECMO), and to provide a reference for further and wider research in the future.Methods: The literatures on ECMO from January 2011 to July 2021 in the Web of Science Core Collection (WOSCC) database were searched, and Citespace5.8.R1 software was used to conduct bibliographic and visual analysis on the literature by country, institution, author and keywords.Results: A total of 5,986 articles were enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In new studies and information updates on LT the works of the authors in Figure 5, guidelines, journals and articles of societies; especially the ISHLT guidelines, should be specially reviewed. In line with the guidelines and other papers published by ISHLT and other societies, it is of lifesaving importance that LT can be applied to patients with indications, the results are reported and published, and new information is produced [25].…”
Section: Accepted Manuscriptmentioning
confidence: 76%
See 1 more Smart Citation
“…In new studies and information updates on LT the works of the authors in Figure 5, guidelines, journals and articles of societies; especially the ISHLT guidelines, should be specially reviewed. In line with the guidelines and other papers published by ISHLT and other societies, it is of lifesaving importance that LT can be applied to patients with indications, the results are reported and published, and new information is produced [25].…”
Section: Accepted Manuscriptmentioning
confidence: 76%
“…In-line with the guidelines and other papers published by ISHLT and other societies, it is of lifesaving importance that LT can be applied to patients with indications, the results are reported and published, and new information is produced. 25…”
Section: Discussionmentioning
confidence: 99%
“…By analyses the keywords, research hotspots and trends can be effectively obtained ( Wang H. et al, 2021 ; Zhang et al, 2021 ). The research trends on mitophagy can be roughly divided into three stages.…”
Section: Discussionmentioning
confidence: 99%
“…Research in the field of ECMO is characterized by ongoing clinical trials and studies aimed at addressing challenges and improving patient outcomes. A 10-year bibliometric study and visualization analysis identified research hotspots and trends in ECMO, providing insights into the evolving landscape of ECMO research [55]. Current and future strategies to monitor and manage coagulation in ECMO patients are also a research focus, given the risk of bleeding and thrombosis complications associated with ECMO [56].…”
Section: Clinical Trials and Studiesmentioning
confidence: 99%